الالتزام التنظيمي وعلاقته بتحسين ونمو مؤسسات ريادة الأعمال - خالد عقاب; البشير زناتي; جمال بن تيشة; عبد الكامل غربي (جامعة الوادي university of eloued, 2024)
"ناولت هذه الدراسة موضوع الالتزام التنظيمي وعلاقته بتحسين ونمو مؤسسات ريادة الأعمال. الهدف الرئيسي كان استكشاف كيف يمكن للالتزام التنظيمي أن يسهم في تعزيز الأداء والابتكار والنمو داخل هذه المؤسسات. لتحقيق هذا الهدف، استخدمت الدراسة منهجية تحليلية تعتمد على مراجعة الأدبيات ذات الصلة وتقييم النماذج النظرية والتطبيقية التي تشرح العلاقة بين الالتزام التنظيمي والأداء التنظيمي. أظهرت النتائج أن الالتزام التنظيمي يلعب دوراً حيوياً في تحسين أداء مؤسسات ريادة الأعمال. الموظفون الذين يشعرون بالتزام قوي تجاه منظمتهم يظهرون مستويات أعلى من الإنتاجية والإبداع، ويكونون أكثر استعداداً للمشاركة في جهود الابتكار والتحسين المستمر. كما أن الالتزام التنظيمي يقلل من معدل دوران الموظفين، مما يوفر تكاليف التوظيف والتدريب، ويعزز من استقرار الموارد البشرية داخل المؤسسة. أوضحت الدراسة أيضاً أن المؤسسات التي تستثمر في تعزيز الالتزام التنظيمي، من خلال خلق بيئة عمل إيجابية وداعمة، تنجح في بناء ثقافة تنظيمية قوية. هذه الثقافة تجذب المواهب الجديدة وتحافظ على الموظفين المتميزين، مما يساهم في تعزيز القدرة التنافسية للمؤسسة والتكيف مع التغيرات السريعة في السوق. ختاماً، توصي الدراسة بأن تركز مؤسسات ريادة الأعمال على تطوير استراتيجيات فعالة لتعزيز الالتزام التنظيمي، مثل توفير برامج تدريب وتطوير مستمرة، وتحسين سياسات الحوافز والمكافآت، وتعزيز التواصل المفتوح بين الإدارة والموظفين. هذه الاستراتيجيات ستسهم في تحقيق نمو مستدام ونجاح طويل الأمد للمؤسسات الريادية. فقـد تناولنـا في الفصـل الأول أهـم المفـاهيم بالالتزام التنظيمي ومؤسسات ريادة الأعمال، في حـين تضـمن الفصـل الثاني دراسة ميدانية، حيث تم الاعتمـاد علـى المـنهج الوصـفي وهذا باسـتخدام الاسـتبيان كـأداة أساسـية. حيـث تم توزيعــه علــى عينــة مــن مؤسسات ريادة الأعمال بالــوادي، تتكــون مــن 52 فــرد وذلــك للحصــول علــى المعلومـات والاسـتعانة لعديـد مـن الأسـاليب الإحصـائية لتحديـد طبيعـة البيـات والاختبـارات المناسـبة لكـل فرضـية.وقد توصلت الدراسة إلى: - توجد علاقة ارتباطية ذات دلالة إحصائية عند مستوى دلالة (0.05α≤)بين الالتزام العاطفي ونمو وتطور مؤسسات ريادة الأعمال بولاية الوادي. - توجد علاقة ارتباطية ذات دلالة إحصائية عند مستوى دلالة (0.05α≤)بين الالتزام الأخلاقي ونمو وتطور مؤسسات ريادة الأعمال بولاية الوادي. - توجد علاقة ارتباطية ذات دلالة إحصائية عند مستوى دلالة (0.05α≤)بين الالتزام المستمر ونمو وتطور مؤسسات ريادة الأعمال بولاية الوادي. - لا توجد فروق ذات دلالة إحصائية عند مستوى دلالة (0.05α≤)بين متوسطات تقديرات أفراد العينة حول الالتزام التنظيمي ومؤسسات ريادة الأعمال تعزى للمتغيرات الشخصية. " "This study investigates the role of organizational commitment in enhancing and fostering the growth of entrepreneurial institutions. The primary objective was to examine how organizational commitment can drive improved performance, innovation, and growth. An analytical approach was adopted, involving a thorough review of relevant literature and an evaluation of both theoretical and practical models that explain the link between organizational commitment and organizational performance. The findings indicate that organizational commitment is pivotal in enhancing the performance of entrepreneurial institutions. Employees who are strongly committed to their organization show higher levels of productivity and creativity and are more likely to participate in innovation and continuous improvement efforts. Additionally, strong organizational commitment reduces employee turnover, resulting in significant savings on recruitment and training costs, and contributes to greater human resource stability within the organization. Furthermore, the study highlights that institutions investing in promoting organizational commitment through creating a positive and supportive work environment are successful in building a strong organizational culture. This culture not only attracts new talent but also retains high-performing employees, thereby boosting the institution's competitive advantage and adaptability to rapid market changes. In conclusion, the study recommends that entrepreneurial institutions focus on developing effective strategies to enhance organizational commitment. These strategies include providing continuous training and development programs, improving incentive and reward systems, and fostering open communication between management and employees. Implementing these strategies will contribute to sustainable growth and long-term success for entrepreneurial institutions. In the first chapter, we discussed the most important concepts of organizational commitment and entrepreneurial institutions, while the second chapter included a field study, relying on the descriptive approach, using a questionnaire as a basic tool. It was distributed to a sample of entrepreneurship institutions in the valley, consisting of 52 individuals, in order to obtain information and to use a number of statistical methods to determine the nature of the data and appropriate tests for each hypothesis. The study concluded:- There is a statistically significant correlation at the significance level (α≤ 0.05) between emotional commitment and the growth and development of entrepreneurial institutions in the state of El Oued. - There is a statistically significant correlation at the level of significance (α≤ 0.05) between moral commitment and the growth and development of entrepreneurial institutions in the state of El Oued. - There is a statistically significant correlation at the level of significance (α≤ 0.05) between continuous commitment and the growth and development of entrepreneurial institutions in the state of El Oued. - There are no statistically significant differences at the level of significance (α≤ 0.05) between the averages of the sample members’ estimates about organizational commitment and entrepreneurial institutions due to personal variables. "
Keywords: الالتزام التنظيمي، المؤسسات الريادية، تعزيز الأداء، الابتكار، الوادي Organizational Commitment; Entrepreneurial Institutions; Performance Enhancement; Innovation; Eloued